Efficient Cooperative Financial Management: Training on Transparent Financial Reporting - Putri, PA Andiena Nindya; Sugianto, Sugianto; Eka, Andi Primafira Bumandava; Susanto, Edy; Siddiqa, Heidi (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Efficient financial management is a key factor in the success of cooperatives. This study aims to evaluate the effectiveness of training in preparing transparent financial statements for cooperative members. The method employed in this research is Community Service (PKM), focusing on providing a comprehensive understanding of basic accounting principles, techniques for preparing financial reports, and the importance of transparency in financial management. Through this training program, participants are expected to enhance their skills in creating accurate and accountable financial statements while understanding the impact of transparency on member trust. The results of the activity indicate a significant improvement in participants' abilities to prepare financial reports and increase transparency, which in turn contributes to better cooperative management.